Between Tides and Knowledge: A Journey through Environmental Education and Mangrove Conservation - Becerra, Melgris José (2024)
This article addresses the exchange of knowledge between university student researchers and students in basic education, particularly between the 7th and 9th grades, in riverside communities in the Paraense Amazon, within the scope of the "Entre Marés" project. This initiative, developed in communities in the municipalities of Maracanã and Magalhães Barata, Pará/Brazil, emerges from a joint effort by students from the Landscape and Environmental Planning Study Group (GEPPAM) at the Federal University of Pará (UFPA). The main objective is to promote environmental awareness towards the appreciation and preservation of natural and cultural heritage in these riverside locations, through an active and participatory interaction between scientific knowledge and local wisdom. The methodological plan focused on the integration of all participating actors. The implementation of a participatory work plan is highlighted, including oral presentations, the production of "speaking maps" by students emphasizing the importance of environmental education, and the identification of areas vulnerable and/or impacted by tourism activities. The collection of seeds and seedlings from local vegetation is also emphasized as part of practical activities, highlighting the importance of community action in preserving coastal ecosystems. This project highlights the importance and potential observed in the dialogue between scientific knowledge and local wisdom as a path toward environmental conservation and sustainability. The results obtained, therefore, reveal the relevance of this collaborative approach in promoting an active environmental consciousness and encouraging preservation practices at the community level.